2014
DOI: 10.1002/adsc.201301147
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐Supported Tripod Triarylphosphane: Application to Transition Metal‐Catalyzed C(sp3)H Borylations

Abstract: A silica-supported tripod triarylphosphane (Silica-3p-TPP), containing a triphenylphosphanetype core tripodally immobilized on the silica surface, allows rhodium-and iridium-catalyzed CA C H T U N G T R E N N U N G (sp 3) À H borylations of amide, urea and alkylpyridine derivatives. The 31 P CP/MAS NMR studies for the coordination behavior of the tripod phosphane towards a rhodium complex indicate efficient site isolation of the each phosphane center, allowing independent mono-P-coordination to the metal cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The accumulated knowledge of the past 20 years, in terms of increased catalyst activity and solvent range, suggests there are likely still gains to be found in the effectiveness of this system. This said, one hugely valid criticism remains: the high cost and scarcity of Ir, which may be offset in the cases of highly efficient or heterogeneous, recyclable systems. The development of undirected 3d metal-based systems, which may replicate and complement Ir borylation chemistry, is therefore an exciting area of growth. Ni, Fe, and dual-metal systems have been developed, but the most general of the new catalysts seem to be Co based, of which the work of Chirik is best known (Scheme ).…”
Section: Case Study: Arene C–h Borylationmentioning
confidence: 99%
“…The accumulated knowledge of the past 20 years, in terms of increased catalyst activity and solvent range, suggests there are likely still gains to be found in the effectiveness of this system. This said, one hugely valid criticism remains: the high cost and scarcity of Ir, which may be offset in the cases of highly efficient or heterogeneous, recyclable systems. The development of undirected 3d metal-based systems, which may replicate and complement Ir borylation chemistry, is therefore an exciting area of growth. Ni, Fe, and dual-metal systems have been developed, but the most general of the new catalysts seem to be Co based, of which the work of Chirik is best known (Scheme ).…”
Section: Case Study: Arene C–h Borylationmentioning
confidence: 99%
“…The above reactions involve radical intermediates I 9 and/or I 4 . Borylation [130][131][132], silylation [133], and amidation [134] of N-adjacent C-H bond of DMAc have been achieved with bis(pinacolato)diboron and Rh or Ir catalysis (Scheme 41a,b), triethylsilyl hydride, Ru catalysis, and tert-butylethylene as the hydrogen acceptor (Scheme 41c), and N-haloimides under blue light irradiation (Scheme 41d). The transition-metal catalysis could involve the C(sp 3 )−H bond oxidative addition to the metal center [135,136] while the photochemical conditions promote the formation of radical I 9 [134].…”
Section: Rc=on(ch 2 )Me Fragmentmentioning
confidence: 99%
“…This stereoselectivity mirrors that reported by Sawamura for pyridine-directed borylation. 6b These products were formed in moderate to good yield, with >20:1 diastereoselectivity. Ether, acetal, tertiary amine, and amide functional groups were tolerated.…”
mentioning
confidence: 94%
“…5 Sawamura et al have reported the Rh- and Ir-catalyzed borylation of alkyl C−H bonds α to the nitrogen of amides or γ to a pyridyl nitrogen. 6 Shi et al have reported the Pd-catalyzed borylation of primary alkyl C−H bonds directed by an amide, 7 and Yu recently reported a similar reaction that includes the borylation of secondary alkyl C−H bonds. 8 Our group reported selective borylation of amines and ethers at the C−H bonds located β to nitrogen and oxygen, due to a set of weak attractive interactions.…”
mentioning
confidence: 99%